Water Physicochemical Variables In The Rancheria River Delta, La Guajira, Colombia - Molina-Bolívar, Geomar Enrique; Nava Ferrer, Mario Lester; Jiménez Pitre, Iris Agustina (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The spatial-temporal dynamic of physical-chemical variables of the water was characterized and monitored in the Ranchería River in the Colombian Guajira. Five sampling stations were chosen, three in the arm The Riíto: Desembocadura (DB), El Mirador (EM) and Villa Fatima (VF), and two stations in the arm Calancalá: Cangrejito (CG) and Valle de los Cangrejos (VC), monthly measurements for one year were made of temperature, dissolved oxygen, salinity, turbidity, alkalinity, total hardness, ammonium, nitrite, nitrate, phosphorus and N/P relationship. The results indicate that the arms have a different dynamics between them. The salinity increased during the study period; it was higher in the stations of the Calancalá; the highest average was recorded in CG with 46.72±13.56 ups., the dissolved oxygen showed a different pattern in both arms, decreased from the rainy season (3.19-4.40 mg./L.) to dry (2.04-3.01 mg./L.) in the Riíto, while the opposite occurred in the arm Calancalá. The pH tended to be higher in the Calancalá with respect to Riito, being significantly different in both arms in the two seasons studied; alkalinity was statistically different in the dry season for both arms. The waters of the Riíto were more turbid (61.39 -81.71 ntu.) with regard to the Calancalá (30.02-30.17 ntu.) in the rainy season. The nutrients nitrogen and phosphorus showed little variability, becoming more notorious during the dry season. A great spatio-temporal variability of the physicochemical variables was evidenced, which distinguishes the two arms of the Ranchería River Delta, as a result of climatic factors and specific features of each arm, which generates an environmental heterogeneity, mainly during the dry season.